Non-Discriminating Atticus Finch in To Kill A Mockingbird - Andrianti, Maria Patrisia (Journal of English Department WM, 2014)
A novel has many values that can be applied in daily life. One of the values is non-discriminating character that can be seen in To Kill A Mockingbird novel. This value teaches the readers how to treat people without prejudice. This paper aims at describing in what ways Atticus Finch demonstrates a non-discriminating character and the factors that influence Atticus Finch to have a non-discriminating character. The writer uses objective approach that focus on intrinsic elements of the novel. The analysis concludes that there are five ways in which Atticus Finch demonstrates his non-discriminating character and three factors that influence Atticus Finch to have a non-discriminating character.